What drives motivated agents? The "right" mission or sharing it with the principal - Hannes Koppel; Tobias Regner (Friedrich Schiller University Jena, 2015)
Motivated agents are characterized by increasing their effort if their work generates not only a monetary return for them but also a benefit for a mission they support. While their motivation may stem from working for their preferred (i.e., the `right') mission, it may also be the principal's choice of the right mission (i.e., a mission preference match) that motivates them. We investigate experimentally to what extent these two motivations are driving the effect of a mission on agent effort. We find that agents care not only about the mission as such but also whether the principal shares this mission. Our analysis estimates the additional effect of a mission preference match to be as big as the effect of just working for the right mission. It seems that the full potential of `motivation by mission' is realized only when principals share as well as support the agents' mission, stressing the importance of the economics of identity in labor market settings.
Keywords: C91; D03; J01; M14; M52; 330; corporate social responsibility; experiment; identity; incentives; labor market; mission; motivated agents; principal agent